Studi Akurasi Sensor Ultrasonik Tipe US-015 Untuk Pengukuran Pasang Surut Air Laut Daerah Bergelombang - Hartoto, Dwi Nanda Putra; Fadly, Romi; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
The technology in observing tides has developed, with the discovery of sensors that can make observations of tides automatically. one of the sensors that can be used for tidal observation is an ultrasonic sensor that works based on the principle of ultrasonic waves. Natural phenomena that occur such as sea level waves can affect the accuracy of tidal readings using ultrasonic sensors. This study aims to design an ultrasonic sensor-based tide instrument that can reduce sea wave interference and calculate the accuracy of the reading results of the instrument. Data collection was observed per 1 second, then the data was divided into several intervals, that is 1 second, 5 minutes, 15 minutes and 30 minutes. The accuracy of the instrument is calculated based on the observed manual data per 30 minute interval, after that the data will be tested for correlation and significance between the variables of closed automatic instrument, automatic open instrument and manual observed. This study produces equipment for automatic tide measurement that can reduce waves with ultrasonic sensors. The results of testing the data from 3 observations obtained accuracy of the closed automatic instrument has better accuracy that is 99.1981%, 99.3007%, 99.3156%. Keywords: Tides, Ultrasonic sensor, Microcontroller, Arduino uno.